The Sandman. Book one - Gaiman, Neil (Sandman, 2022)
Now a Netflix TV series, the first volume of Neil Gaiman's graphic novel masterpiece returns in a new edition! One of the most popular and critically acclaimed graphic novels of all time, Neil Gaiman's award-winning masterpiece The Sandman set the standard for mature, lyrical fantasy in the modern comics era. Illustrated by an exemplary selection of the medium's most gifted artists, the series is a rich blend of modern and ancient mythology in which contemporary fiction, historical drama, and legend are seamlessly interwoven. The Sandman Vol. 1: Preludes Nocturnes collects issues #1-8 of the original run of The Sandman, beginning an epic saga unique in graphic literature and introducing readers to a dark and enchanting world of dreams and nightmares--the home of Morpheus, the King of Dreams, and his kin, the Endless. The stories introduce Dream in the opening arc More than Rubies, followed by the debut of fan-favorite character Death in The Sound of Her Wings. With The Sandman television adaptation debuting on Netflix, and the audio drama unfolding on Audible, explore the comic book classic that started it all!